2019
DOI: 10.24996/ijs.2019.60.9.9
|View full text |Cite
|
Sign up to set email alerts
|

Study the association between IL-17 level and autoimmune antibodies in hypo and hyper thyroidisms patients

Abstract: The current study included measuring the level of IL-17A and IL-17F and some autoimmune antibodies related to the thyroid gland in case of  hypo and hyperthyroid in Iraqi patients to evaluate the correlation between all the measured parameters in this study.The study has been carried out in AL-Kindey Endocrine Gland and Diabetic Center in Baghdad during the period between February 2018 and May 2018, included:  88 patients were divided into three groups, The first group composed of 30 patients of Hypothyroidism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Therefore, the level of anti-TG in hyperthyroid patients is much greater than in hypothyroid patients (364.2 ± 46.96 vs 257.5 ± 28.91 IU/ml). The results agreed with the study of (20), which demonstrated the level of anti-TG antibodies in hyperthyroidism patients was highly significant (P < 0.01) than in a control group, and also in the hypothyroidism patients group. Thyroid autoimmunity may play the role in the clinical symptoms of HT, as seen by elevated TgAb level in Hashimoto's Thyroiditis patients (10).…”
Section: Resultssupporting
confidence: 90%
“…Therefore, the level of anti-TG in hyperthyroid patients is much greater than in hypothyroid patients (364.2 ± 46.96 vs 257.5 ± 28.91 IU/ml). The results agreed with the study of (20), which demonstrated the level of anti-TG antibodies in hyperthyroidism patients was highly significant (P < 0.01) than in a control group, and also in the hypothyroidism patients group. Thyroid autoimmunity may play the role in the clinical symptoms of HT, as seen by elevated TgAb level in Hashimoto's Thyroiditis patients (10).…”
Section: Resultssupporting
confidence: 90%
“…For autoantibodies status, it was found that about half of the patients (49.3%, n=37) were positive for both anti-TG and anti-TPO while the remaining patients were positive for either of them. In total, and as shown in table (1), 92 % (n=69) of patients were positive for anti-TPO with a median of 282.9 (range: 41.6-1154.0 IU/ml) and 57.3 % (n=43) of them were positive for anti-TG with a median of 471.7 (range: 122.3 -2998.9 IU/ml). Individuals in the control group had either undetectable concentrations of these autoantibodies or their concentrations were below the cut-off values of 40 IU/ml and 120 IU/ml for anti-TPO and anti-TG respectively.…”
Section: Resultsmentioning
confidence: 89%
“…Triiodothyronine (T3) and Thyroxine (T4) are hormones secreted exclusively from the thyroid gland and required by all metabolically active cells; therefore, deficiency or impaired activity of these hormones can result in hypothyroidism which is a common disorder of the endocrine system with a wide range of effects on the body [1]. Hypothyroidism can be presented as Hashimoto's thyroiditis (HT) which is a form of autoimmune thyroid disease (AITD) resulting from T cell-mediated organ-specific immune response against the thyroid gland resulting from immune system deregulation [2].…”
Section: Introductionmentioning
confidence: 99%
“…Anti-thyroid globulin has a positive association with IL-17f while anti-thyroid peroxidase has an association with IL-17a in a hypothyroid patient. Hence, a higher level of IL-17 leads to an increase in thyroid autoantibodies which might damage the thyroid gland (26). In India, vitiligo disease is linked with thyroid disorders which makes it necessary to screen vitiligo patients for autoimmune thyroid diseases (AITD) on regular basis (1).…”
Section: Immunological Parametersmentioning
confidence: 99%